EFFECT OF SYZYGIUM AROMATICUM L. ESSENTIAL OIL EXTRACT AGAINST PATHOGENIC CANDIDA.ALBICANS IN-VITRO - Ban M.A.,; O. M. S. Ibrahim, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Candida albicans is an universal fungi, belong to the phylum Ascomycota, the infection caused by Candida albicans is called candidiasis. The study aimed to evaluate the Syzygium aromaticum extract as antifungal activity and fungicidal against C.albicans. Furthermore, gas chromatography-mass spectrometry (GC-MS) analysis was performed to determine active components of clove oil which indicated the presence of eugenol (41.24%), followed by caryophyllene (18.36%) . The disc diffusion method and minimum inhibitory concentration was done to evaluate the anti-candidal activity of different S.aromaticum concentration. Extract with S. aromaticum yield percentage of 46.6 %. The in-vitro anti-candidal extract exhibited the highest antifungal activity against C. albicans, with inhibition zone diameters of 22.0 mm at 0.5mg/disc. The minimum inhibitory concentration of the extract was 1mg/ml against C. albicans, while the minimum fungicidal concentration was 2mg/ml.